Henry Van de Velde : en zijn tijdgenoten - Van de Velde, Ronny; Van de Velde, Jessy; Ceuleers, Jan (Knokke-Zoute : Galerie Ronny Van de Velde, 2018)
Van de Velde, Henry ; Luyten, Jan Hendrik ; Abry, Leon ; Artan de Saint-Martin, Louis ; Charlet, Franz ; Claus, Emile ; De Braekeleer, Henri ; Ensor, James ; Evenepoel, Henri ; Frédéric, Léon ; Joors, Eugène ; Laermans, Eugène ; Lambeaux, Jef ; Lamorinière, Frans ; Lemmen, Georges ; Linnig Jr, Willem ; Mellery, Xavier ; Meunier, Constantin ; Morren, George ; Ooms, Karel ; Redon, Odilon ; Rodin, Auguste ; Rops, Felicien ; Serrurier Bovy, Gustave ; Stevens, Alfred ; Stobbaerts, Jan ; Toorop, Jan ; Thorn Prikker, Johan ; Van Beers, Jan ; van der Ouderaa, Piet Jan ; Van der Stappen, Charles ; Verheyden, Isidore ; Verstraete, Theodoor ; Verlat, Charles ; Vogels, Guillaume ; Menzel, Willia
Henry van de Velde en zijn tijdgenoten, Galerie Ronny Van de Velde, Knokke-Zoute, 17 februari tot en met 15 april 2018
boek